2006
DOI: 10.1159/000095124
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Paraoxonase and Oxidative Stress in Adolescents with Uraemic, Essential or Obesity-Induced Hypertension

Abstract: Background/Aims: Paraoxonase 1 (PON1) is associated with high-density lipoproteins in the plasma, and is capable of hydrolysing oxidized lipids and preventing the oxidation of low-density lipoproteins. Oxidative stress and the PON1 (activity and Q192R polymorphism) were analysed in adolescent patients with essential (n = 49) or obesity-induced hypertension (n = 79), uraemic patients (n = 20), and also in obese normotensive patients (n = 60) and age-matched controls (n = 57). Methods: The PON1 activity was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…A study conducted in Portuguese women showed an association of the R allele with a higher risk of obesity [26], whereas a study in Mexican adults revealed no association between the variant and risk of obesity [25]. Another study failed to find any association of the SNP with obesity in adolescents [68]. Our group recently published a study carried out in prepubertal children that also confirmed the lack of an effect of Q192R on childhood obesity risk [37].…”
Section: Enzymatic Antioxidant Defense Genesmentioning
confidence: 99%
“…A study conducted in Portuguese women showed an association of the R allele with a higher risk of obesity [26], whereas a study in Mexican adults revealed no association between the variant and risk of obesity [25]. Another study failed to find any association of the SNP with obesity in adolescents [68]. Our group recently published a study carried out in prepubertal children that also confirmed the lack of an effect of Q192R on childhood obesity risk [37].…”
Section: Enzymatic Antioxidant Defense Genesmentioning
confidence: 99%
“…In this reexamination of our group of MS subjects, we calculated also the TBARS/NO x ratio that, up to now, has been evaluated in preeclampsia [29], in juvenile essential hypertension [30], and in hypertensive adolescents with obesity or uraemia [31, 32]. In MS the TBARS/NO x ratio may be considered as an integrated marker of plasma lipid peroxidation and degree of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, increased levels of oxidized glutathione (GSSG), elevated ratios of oxidized/reduced glutathione (GSSG/GSH), decreased GSH levels, impaired GSH regeneration and a more pronounced lipid peroxidation have been demonstrated in adolescent hypertensives [43]. However, no differences were observed in the paraoxonase-1 (PON1) activities, PON1 Q192R genotype or homocysteine levels in this patient group, irrespective of the degree of obesity [44]. Next, we set out to examine whether a short-term antihypertensive treatment could reveal differences in markers of oxidative stress and endothelial dysfunction between lean or obese hypertensive adolescents [45].…”
Section: Primary Hypertension and Obesity In Childhood: Two Interrelasupporting
confidence: 66%